Head and Neck Squamous Cell Carcinoma in Western Uganda: Disease of Uncertainty and Poor Prognosis - Nabukenya, Jamilah; Hadlock, Tessa A.; Arubaku, Wilfred (Sage, 2018)
Objectives Patients with head and neck squamous cell carcinoma (HNSCC) have symptoms that masquerade as benign conditions, resulting in late presentations. The objective is to describe characteristics and stages of patients with HNSCC and document their prognosis from clinical experience in western Uganda. Study Design Cross-sectional study with clinical follow-up. Setting Mbarara Regional Referral Hospital. Subjects and Methods Fifty-one participants were recruited from February to July 2016. A questionnaire was used for patient characteristics, and staging, serologic studies, biopsy for histopathology, and immunohistochemistry were investigated. Staging was subclassified as early (stage I and II) and late (stage III and IV). Analysis was done with Fisher’s exact test. Results Of 51 participants, 44 (86.5%) were male; the group had a mean age of 57.7 years, and 41 (80.1%) presented with late stage. Of 10 participants who presented with early stage, 6 (60%) had laryngeal HNSCC. The pharynx was ranked as the highest subsite (n = 19, 37.3%), followed by the oral cavity (n = 9, 17.6%), the larynx (n = 9, 17.6%), an unknown primary (n = 8, 15.7%), and sinonasal area (n = 6, 11.8%). Tobacco smoking, alcohol consumption, and prior use of traditional remedy were common characteristics among participants. Moderate differentiation was the most common grade (n = 23, 45.1%). Helicobacter pylori, Epstein-Barr virus, human immunodeficiency virus, and human papilloma virus type 16 were identified among 51 participants. However, none could afford referral for radiotherapy; hence, 1-year survival was 4%. Conclusion The majority of our patients with HNSCC present at late stage, and the prognosis is poor. There is great need for preventative community-based education and early screening services to save our population.
Keywords: head and neck squamous; cell carcinoma; Uganda